2003
DOI: 10.1590/s0037-86822003000500001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular function in elderly patients with chronic chagasic cardiopathy

Abstract: The objective of this work was to verify the degree and type of heart damage of elderly chagasic patients seen at an outpatient referral center and to compare them with the changes found in young chagasic patients with a similar degree of heart damage. Elderly and young patients without advanced cardiopathy presented good functional behavior. Elderly patients with advanced cardiopathy had more ventricular premature beats (VPB) in 24 h and less functional capacity in the exercise test than young patients of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…Because there is no undisputable effective treatment for chronic infection, despite the effectiveness of the control measures, the disease might remain a public health problem for some decades among older subjects, through the operation of a cohort effect [4]. The effect of T. cruzi infection on the elderly has hardly been studied [4][5][6][7][8][9] and deserves more attention from the scientific community and from policy makers. Impairment of cardiac vagal modulation has been consistently reported in ChD [10][11][12][13] and may be related to both autoimmune and inflammatory mechanisms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because there is no undisputable effective treatment for chronic infection, despite the effectiveness of the control measures, the disease might remain a public health problem for some decades among older subjects, through the operation of a cohort effect [4]. The effect of T. cruzi infection on the elderly has hardly been studied [4][5][6][7][8][9] and deserves more attention from the scientific community and from policy makers. Impairment of cardiac vagal modulation has been consistently reported in ChD [10][11][12][13] and may be related to both autoimmune and inflammatory mechanisms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, more recent studies have shown that the clinical manifestations of ChD in old ages are similar -or even worse -than those observed in young adults [9][10][11][12]. Indeed, an analysis of mortality and public hospitalization rates in Brazil in the last decades showed that a substantial toll of the burden of T. cruzi infection affected older adults [4], suggesting that ChD in the elderly might be more severe and potentially lethal than suspected in earlier studies.…”
mentioning
confidence: 99%
“…The present burden of T. cruzi infection for the elderly living in areas where the transmission has been interrupted has been scarcely studied and deserves more attention from the scientific community and from policy makers [23][24][25]. The effect of aging over autonomic dysfunction should also be thoroughly scrutinized.…”
Section: Dear Sirmentioning
confidence: 99%